Terapi CBT terhadap Penurunan Depresi pada Pasien Gagal Ginjal Kronik - Ida Wahyuni; Bergita Dumar; Tri Nily Sulayfiyah; Dwi Intan Pakuwita Ar (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of CBT on reducing depression in patients with Chronic Kidney Failure (CKD). The study used a quasi-experimental pre-post test design without a control group and was conducted in the hemodialysis ward of Abdur Rahem Hospital, Situbondo. The sample size was 39 patients in the treatment group and 39 in the control group, selected through purposive sampling. The Beck's Depression Inventory-II (BDI-II) was used to measure depression. The results showed a significant reduction in depression levels in both groups (p = 0.001), but a greater reduction occurred in the treatment group, with an average N-gain of 45.44%, compared to the control group, which only achieved 17.54% (p = 0.000). These findings indicate that CBT is effective in reducing depression levels in CKD patients undergoing hemodialysis. In conclusion, CBT therapy is recommended as a routine psychological intervention to improve the mental well-being and quality of life of CKD patients. Keywords: Cognitive Behavior Therapy, Depression, Chronic Kidney Failure